2020
DOI: 10.1007/s40265-020-01322-y
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Approaches Towards a Functional Cure of HIV/AIDS

Abstract: Therapeutic approaches towards a functional cure or eradication of HIV have gained renewed momentum upon encouraging data emerging from studies in SIV monkey models and recent results from human clinical studies. However, a multitude of questions remain to be addressed, including how to deal with the latent viral reservoir, how to boost the host immune response to the virus and what the hurdles are to reach relevant viral compartments in the body. Advances have been made especially with regard to identifying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 92 publications
(102 reference statements)
0
22
0
Order By: Relevance
“…HIV infection is a chronic infection that persists in lymphoid tissues even in the context of antiretroviral therapy causing profound tissue-specific alterations (15,55,(78)(79)(80). This characteristic of HIV pathogenesis has prompted several cure strategies aiming at viral reservoir elimination to be developed over the past years (81). In this context, we designed a panel that leverages the analytical strength of the RNAscope in situ hybridization platform (ACD) and resolving power of confocal microscopy for topological examination and quantification of HIV-specific RNA in tissues.…”
Section: Detection Of Cells Harboring Actively Transcribing Hivmentioning
confidence: 99%
“…HIV infection is a chronic infection that persists in lymphoid tissues even in the context of antiretroviral therapy causing profound tissue-specific alterations (15,55,(78)(79)(80). This characteristic of HIV pathogenesis has prompted several cure strategies aiming at viral reservoir elimination to be developed over the past years (81). In this context, we designed a panel that leverages the analytical strength of the RNAscope in situ hybridization platform (ACD) and resolving power of confocal microscopy for topological examination and quantification of HIV-specific RNA in tissues.…”
Section: Detection Of Cells Harboring Actively Transcribing Hivmentioning
confidence: 99%
“…Therefore, even in the hypothetical case that the most optimized therapeutic vaccine is obtained, this will probably not be enough to eliminate the reservoir. Co-administration of a therapeutic mRNA vaccine with drugs that could reactivate the reservoir of HIV (Kick-and-Kill strategy), immune checkpoint inhibitors, or broadly neutralizing antibodies are all promising approaches [ 92 ]. Maybe the functional cure of HIV is in one of those combined treatments, but first, every single strategy will need to be optimized separately to make a combination successful.…”
Section: Discussionmentioning
confidence: 99%
“…As it is now clear that a vaccine alone would not be enough to cure HIV, attention has turned into combining vaccines with other treatments, attacking the virus from multiple sides [ 91 , 92 ]. A strategy that has received much attention in recent years is the combination of therapeutic vaccines with latency reversal agents (LRA) and blocking antibodies.…”
Section: Mrna-based Hiv Functional Cure Strategiesmentioning
confidence: 99%
“…One of the aims of the HIV-1 functional cure is to identify small molecules that can be combined with ART to delay or halt virus replication, reactivation, and replenishment of the latent reservoir (59,60). Having shown that diminished levels of endogenous H2S is associated with HIV-1 reactivation, we next examined if elevating H2S levels using a small-molecule H2S donor-GYY4137 sustains HIV-1 latency.…”
Section: A Small-molecule H2s Donor Diminished Hiv-1 Reactivation and Viral Replicationmentioning
confidence: 99%